2006
DOI: 10.1186/1297-9686-38-3-297
|View full text |Cite
|
Sign up to set email alerts
|

Fatness QTL on chicken chromosome 5 and interaction with sex

Abstract: -Quantitative trait loci (QTL) affecting fatness in male chickens were previously identified on chromosome 5 (GGA5) in a three-generation design derived from two experimental chicken lines divergently selected for abdominal fat weight. A new design, established from the same pure lines, produced 407 F2 progenies (males and females) from 4 F1-sire families. Body weight and abdominal fat were measured on the F 2 at 9 wk of age. In each sire family, selective genotyping was carried out for 48 extreme individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…The assignment of the chicken Dicer gene to chromosome 5 at 1040 cRs is consistent with the chicken and human comparative maps and supports the conservation of synteny between the GGA5 and the human chromosomes (Appendix 1). Previous results indicated that a quantitative trait locus (QTL) affecting fatness in male chicken is identified on chromosome 5 (GGA5), and the female fatness QTL is assigned to less than 8 Mb at the distal part of GGA5 (Abasht et al, 2006). Dicer is a possible positional candidate gene.…”
Section: Resultsmentioning
confidence: 99%
“…The assignment of the chicken Dicer gene to chromosome 5 at 1040 cRs is consistent with the chicken and human comparative maps and supports the conservation of synteny between the GGA5 and the human chromosomes (Appendix 1). Previous results indicated that a quantitative trait locus (QTL) affecting fatness in male chicken is identified on chromosome 5 (GGA5), and the female fatness QTL is assigned to less than 8 Mb at the distal part of GGA5 (Abasht et al, 2006). Dicer is a possible positional candidate gene.…”
Section: Resultsmentioning
confidence: 99%
“…Sex specific and fat related QTL have been described on chromosome 5 in chicken [33] and on several chromosomes in mouse [34]. Gene expression studies in male and female F 2 mice have shown a large degree of sexually dimorphic gene expression in several tissues [35,36].…”
Section: Resultsmentioning
confidence: 99%
“…Our preliminary analysis of the liver transcriptome in the FL and LL chickens during juvenile development revealed 1,805 differentially expressed (DE) genes [3]. Quantitative trait loci (QTL) analyses of an FL x LL intercross identified a major QTL for abdominal fatness at the distal end of chromosome 5 ( GGA 5) [16,17,33]. Further, the expression quantitative trait loci (eQTL) analysis of GGA 5, involving a three generation intercross of the FL x LL chickens, identified variations in expression of 660 hepatic genes that were correlated with abdominal fatness traits [19].…”
Section: Introductionmentioning
confidence: 99%